Emergence of the pointer basis through the dynamics of correlations - Cornelio, M. F.; Farías, O. Jiménez; Fanchini, F. F. [UNESP]; Frerot, I.; Aguilar, G. H.; Hor-Meyll, M. O.; De Oliveira, M. C.; Walborn, S. P.; Caldeira, A. O.; Ribeiro, P. H. Souto (American Physical Society (APS), 2012)
We use the classical correlation between a quantum system being measured and its measurement apparatus to analyze the amount of information being retrieved in a quantum measurement process. Accounting for decoherence of the apparatus, we show that these correlations may have a sudden transition from a decay regime to a constant level. This transition characterizes a nonasymptotic emergence of the pointer basis, while the system apparatus can still be quantum correlated. We provide a formalization of the concept of emergence of a pointer basis in an apparatus subject to decoherence. This contrast of the pointer basis emergence to the quantum to classical transition is demonstrated in an experiment with polarization entangled photon pairs. © 2012 American Physical Society.